Sorption of Athabasca vacuum residue constituents on synthetic mineral and process equipment surfaces from mixtures with pentane - Xing, Cheng; Hilts, Robert; Shaw, John M. (My University, 2010)
Deposition of organic material on mineral and process equipment surfaces poses production, transport, and refining challenges for the petroleum industry. For high-asphaltene content hydrocarbon resources, such as bitumen, deposits are frequently assumed to be asphaltene rich. In this work, deposits formed from Athabasca vacuum residue (AVR) comprising 32 wt % asphaltenes + pentane mixtures on acidic (FeS, SiO2) and basic (Fe2O3/FeOOH/FeO, Ni/NiO/NiOH) substrates are analyzed using X-ray photoelectron spectroscopy. Control experiments with pure compounds are used to confirm experimental protocols and to address substrate contamination, which interferes with deposit composition measurements, if the organic deposit is thin or surface coverage is partial. Substrate properties are found to affect both deposit thickness and deposit composition. On basic substrates, deposits are thinner and are enriched in sulfur relative to AVR. On acidic substrates, deposits are thicker and are sulfur deficient relative to AVR, even though asphaltenes, which are rich in sulfur, sorb more strongly on acidic substrates in the absence of competition from other species. Deposit composition was also found to be invariant with the composition and phase behavior of the AVR + pentane mixtures. These results were not expected.
Keywords: acid-base properties; maya crude oil; asphaltene precipitation; naphthenic acids; mass-spectrometry